2015
DOI: 10.1016/j.jalz.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Imaging‐based enrichment criteria using deep learning algorithms for efficient clinical trials in mild cognitive impairment

Abstract: The Mild Cognitive Impairment (MCI) stage of AD may be optimal for clinical trials to test potential treatments for preventing or delaying decline to dementia. However, MCI is heterogeneous in that not all cases progress to dementia within the time frame of a trial, and some may not have underlying AD pathology. Identifying those MCIs who are most likely to decline during a trial and thus most likely to benefit from treatment will improve trial efficiency and power to detect treatment effects. To this end, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 28 publications
(56 reference statements)
0
51
0
Order By: Relevance
“…However, a trial enrichment strategy using ApoE status would require caution because a recent study has reported that ApoE ɛ 4 carriers have a higher risk of amyloid-related imaging abnormalities than ApoE ɛ 4 non-carriers in clinical trials of immunotherapy for reducing cerebral amyloid burden using bapineuzumab [61]. For ApoE ɛ 4 non-carriers, on the other hand, other clinical enrichment strategies based on a machine learning method that handles data from imaging biomarkers such as those of MRI and/or PET could enrich clinical trials by enabling the selection of participants who will show future cognitive and neural decline [62]. …”
Section: Discussionmentioning
confidence: 99%
“…However, a trial enrichment strategy using ApoE status would require caution because a recent study has reported that ApoE ɛ 4 carriers have a higher risk of amyloid-related imaging abnormalities than ApoE ɛ 4 non-carriers in clinical trials of immunotherapy for reducing cerebral amyloid burden using bapineuzumab [61]. For ApoE ɛ 4 non-carriers, on the other hand, other clinical enrichment strategies based on a machine learning method that handles data from imaging biomarkers such as those of MRI and/or PET could enrich clinical trials by enabling the selection of participants who will show future cognitive and neural decline [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Suk et al (2014) also proposed a generative deep learning to integrate structural and functional patterns inherent in MRI and PET, respectively, by learning shared representations. Similarly, Ithapu et al (2015) also devised a deep learning algorithm called a randomized denoising auto-encoder marker to integrate multimodal data of PET and MRI. However, due to complex composition of non-linear patterns in deep learning, it still remains challenging to interpret the learned representations.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, classification frameworks can be used to develop imaging markers or indices (Davatzikos et al, 2008) with high sensitivity and specificity in individuals (Sajda, 2006) that can summarize the imaging profile of a subject into a single meaningful value (Habes et al, 2016b). This creates a more individualized, patient-tailored approach (Ithapu et al, 2015), which is imperative in the current age of personalized medicine because it allows further consideration of genetic or life-style risks, by utilizing advanced computational power (Habes et al, 2016a; Habes et al, 2016b; Habes et al, 2016c). …”
Section: Introductionmentioning
confidence: 99%